Bulk store as an effort to reduce marine debris in Bajo Pulau - Aziz Ali Haerulloh; Hazman Hiwari (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
Damage to coastal ecosystems and shallow waters of the Bajo Pulau Village, Sape Sub-district, Bima District, West Nusa Tenggara Province is caused by the accumulation of household waste that is not managed by the community from year to year. It resulted in a reduction in the quality of seawater. This study examines the various factors behind it and synthesizes the solution to the problem by proposing a bulk store. The research method used is descriptive-analytic with a qualitative approach. Data collection was carried out by observation, field studies, literature studies, and interviews. The results showed that Indonesia (as the largest archipelagic country) has a low interconnectivity level. It causes small islands to be vulnerable to environmental degradation. This vulnerability is also caused by the lack of a business system that considers sustainable environmental capabilities. Therefore, it is necessary to reduce the amount of household waste scattered on land and in the sea that threatens the surrounding ecosystem with the concept of a minimal garbage collection facility based on a cooperative system.